2013
DOI: 10.1155/2013/134163
|View full text |Cite
|
Sign up to set email alerts
|

The Strength-Interval Curve in Cardiac Tissue

Abstract: The bidomain model describes the electrical properties of cardiac tissue and is often used to simulate the response of the heart to an electric shock. The strength-interval curve summarizes how refractory tissue is excited. This paper analyzes calculations of the strength-interval curve when a stimulus is applied through a unipolar electrode. In particular, the bidomain model is used to clarify why the cathodal and anodal strength-interval curves are different, and what the mechanism of the “dip” in the anodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 54 publications
6
17
0
Order By: Relevance
“…This finding may underlie previous suggestions of the importance of vessels in secondary source formation [4]; however, given the relatively higher field strengths required for break excitation formation [28, 29], such a vessel-mediated mechanism may only be of significance during stronger (conventional) defibrillation protocols, and less so during low voltage protocols.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This finding may underlie previous suggestions of the importance of vessels in secondary source formation [4]; however, given the relatively higher field strengths required for break excitation formation [28, 29], such a vessel-mediated mechanism may only be of significance during stronger (conventional) defibrillation protocols, and less so during low voltage protocols.…”
Section: Discussionsupporting
confidence: 68%
“…Our analysis suggests that vessels may still play an important role in low-energy defibrillation due to the close proximity of de- and hyper-polarised regions around the vessel, which we have shown is augmented by the presence of the vessel wall. Such proximity of regions of opposite polarity may facilitate break excitations, similar to the mechanism for unipolar stimulation [28, 29], allowing vessels to capture intramural tissue that is relatively refractory.…”
Section: Discussionmentioning
confidence: 99%
“…8 The first is electrotonic interaction of adjacent regions of depolarization and hyperpolarization. Dekker 3 identified four mechanisms of excitation: cathode make, cathode break, anode make, and anode break.…”
Section: Introductionmentioning
confidence: 99%
“…Computational bidomain simulations and experimental optical mapping experiments have shown agreement with predictions of SI curves for different polarities of applied stimulus (anodal or cathodal) (Kandel and Roth, 2013). SI curves are produced by applying a premature S 2 stimulus of a known strength to the tissue at a given instant of refractoriness, i.e., at a specific time following the S 1 paced beat.…”
Section: Methodsmentioning
confidence: 62%
“…The mechanisms by which relatively refractory cardiac tissue may be re-excited by a premature unipolar stimulus has been investigated in detail both in computational bidomain studies (Bray and Roth, 1997; Kandel and Roth, 2013, 2014) and corresponding optical mapping experimental work (Sidorov et al, 2005). These studies have demonstrated that the application of a unipolar stimulus to cardiac tissue induces a characteristic dog-bone VE pattern, consisting of neighboring de/hyperpolarization.…”
Section: Methodsmentioning
confidence: 99%